Model Pemetaan Wisata Halal Sebagai Upaya Peningkatan Kunjungan di Banda Aceh - Ihsanuddin Ihsanuddin; Abdus Salam; Fauzan Putraga Al Bahri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2019)
Halal tourism in Indonesia has good economic prospects as part of the national tourism industry. The tourism industry aims not only to provide material and psychological aspects for tourists themselves but also to contribute to increase government revenue. Halal Tourism Mapping System is basically a form of mapping using Google's advanced features and maps as an effort to collect data mapping of halal destination data in order to become a media and promotion for halal tourism search with the label